Using the Practical, Robust Implementation and Sustainability Model to inform meaningful partner engagement and the selection of implementation strategies to increase colorectal cancer screening in federally qualified health centers - Nodora, Jesse; Gupta, Samir; Hurst, Samantha; James, Aimee S.; Rabin, Borsika A. (Frontiers in Public Health, 2025)
Engaging community partners in research meaningfully can guide effective implementation efforts. This approach is particularly crucial when we work with complex, multilevel programs in low-resource settings that serve diverse populations. The application of dissemination and implementation science theories, models, and frameworks to facilitate the iterative, multilevel engagement of partners in selecting and optimizing implementation strategies is not commonly described in the literature. In collaboration with three federally qualified health centers in San Diego County, we utilized the Practical, Robust Implementation and Sustainability Model (PRISM), which is a contextually expanded version of the widely used Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework, to guide partner-engaged data collection on processes, resources, facilitators, and barriers for colorectal cancer (CRC) screening. We gathered implementation-relevant information from each FQHC, including partner introductory meetings, an Agile Science workshop, secondary data collection, surveys, and in-depth interviews. Insights from the PRISM domains led to the development of process maps that guided the selection of implementation strategies to support the use of evidence-based interventions for CRC screening.